Jumping the Abyss : Marriner S. Eccles and the New Deal, 1933-1940 - Nelson, Mark Wayne (Book collections on Project MUSE., 2017)
"Marriner Eccles was a key figure in the formulation and implementation of Franklin D. Roosevelt's New Deal. Mark Nelson calls him, "one of the most important public officials in the history of the United States." Eccles might be recognized, at least by some in Utah, as one of the state's more significant twentieth-century native sons, but neither here nor elsewhere is the degree of his historical importance widely appreciated. He exercised his influence from inside the Civil Works Administration and the Treasury Department, but especially as chairman of the Federal Reserve. While previous authorized books on Eccles have been published, this is the first to examine independently his public career; his public roles, activities, and ideas. As Nelson explains early on, it is as much as anything a study of the New Deal through the person of Eccles. It is not intended as a biography per se, so there is less on Eccles's personal life and roots, and more on the roots of his philosophy"--Provided by publisher.